Articular Repair/Regeneration in Healthy and Inflammatory Conditions: From Advanced In Vitro to In Vivo Models. (6th March 2020) - Teixeira, José H.; Pereira, Catarina Leite; Almeida, Maria Inês; Teixeira, Graciosa Q.; Gonçalves, Raquel M.; Barbosa, Mário A.; Santos, Susana G.
Abstract: The burden of chronic inflammatory diseases of joints and the spine is increasing with population ageing and unhealthy lifestyles. Articular cartilage and intervertebral discs (IVDs) are avascular and aneural tissues with abundant extracellular matrix, low cell density, and reduced regenerative capacity after damage or degeneration. The most advanced in vitro and ex vivo cell‐/tissue‐/biomaterial‐based models and technologies to improve physiological mimicry are discussed, focusing on the impact of inflammation on articular repair/regeneration. In addition, in vivo models, developed to study cartilage and IVD repair/regeneration are addressed. While animal models continue to provide crucial mechanistic and preclinical data, more advanced and robust in vitro/ex vivo cartilage and IVD models, with appropriate extracellular matrix cues and allowing for cellular crosstalk, have seen an exponential growth in the last decade. Due to the complexity of articular microenvironments, adequate in vitro/ex vivo/in vivo models are essential to study the molecular mechanisms underlying articular diseases and develop new therapies for repair/regeneration. Abstract : Chronic inflammatory articular disorders are a major cause of disability, and appropriate study models remain a research challenge. Biomaterials are used to build in vitro models and are tested using in vitro, ex vivo, and in vivo models. Recent advanced in vitro, ex vivo, and in vivo models of articular cartilage and intervertebral disc are reviewed, focusing on inflammation.